Animal crackers in my … book? Effects of shared reading on parents' memory for product placement in children's books. Issue 3 (2nd September 2018) - Holiday, Steven; Davies, John J.
ABSTRACT: The unique combination of characteristics that contribute to the shared reading of children's picture books foster involvement, engagement, and communication, and result in socialization and development. They also have the potential to make readers susceptible to product placements used in the medium. Currently research on product placement spans almost every medium, with the notable exception of children's picture books, where research on the practice has been underserved despite its existing presence. The present study recognizes the combination of multi-sensory and social context encoding that takes place during shared reading in this medium and explores how cognitive busyness arising from parent-child engagement with the narrative may inhibit persuasion knowledge while reading children's books. Using a laboratory experiment and quantitative statistical analysis, the present study demonstrates that shared reading positively affects parents' recollection of product placements in children's picture books. It also discusses theoretical and practical implications of product placement recollection.